Perceptual-cognitive skill and the in-situ performance of soccer players - van Maarseveen, M. J. J.; Oudejans, R. R. D.; Mann, D. L.; Savelsbergh, G. J. P. (The Quarterly Journal of Experimental Psychology, 2017)
Many studies have shown that experts possess better perceptual-cognitive skills than novices (e.g., in anticipation, decision making, pattern recall), but it remains unclear whether a relationship exists between performance on those tests of perceptual-cognitive skill and actual on-field performance. In this study, we assessed the in-situ performance of skilled soccer players and related the outcomes to measures of anticipation, decision-making, and pattern recall. In addition, we examined gaze behaviour when performing the perceptual-cognitive tests to better understand whether the underlying processes were related when performing those perceptual-cognitive tasks. The results revealed that on-field performance could not be predicted on the basis of performance on the perceptual-cognitive tests. Moreover, there were no strong correlations between the level of performance on the different tests. The analysis of gaze behaviour revealed differences in search rate, fixation duration, fixation order, gaze entropy, and percentage viewing time when performing the test of pattern recall, suggesting that it is driven by different processes to that used for anticipation and decision making. Altogether, the results suggest that the perceptual-cognitive tests may not be as strong determinants of actual performance as may have previously been assumed